Digital Currency Studies In Islamic Perspective - Bedjo Santoso; MA Irfan Rahmana; Atin Anggraini Surono (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2021)
This study aims to determine the best type of Digital currency according to Islam. This study uses the Analytical Hierarchical Process (AHP) method by developing several alternative digital currencies and attributes (indicators). In addition, this study also uses deductive qualitative analysis. Respondents in this study amounted to 100 people with the sampling technique Area Stratified Purposive Sampling and several selected respondents were interviewed. The results show that Gold-based Digital Money is the best type of Digital currency according to Islam. The main attribute of ownership in Gold-based Digital Money is Usury abolishment capability. Other factors are Gharar Eraducation, Maysir Eraducation, Justice / Fairness Principles, Medium of exchange, Measurement of value, Store of value and Differed payment instrument. In addition, this model can accommodate 7 criteria for the role of currency in the economy.